Growth and Inflation Forecasts for Germany : An Assessment of Accuracy and Dispersion - Ulrich Fritsche; Jörg Döpke (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
Based on a panel of German professional forecasts for 1970 to 2003 we find that growth and inflation forecasts are unbiased and weakly, but not strongly efficient. Besides the effect of diverging forecasting dates, no other substantial differences in forecasting quality are found among forecasters. We argue that it is not always advisable to listen to the majority of forecasters. The dispersion of forecasts correlates positively with the volatility of macroeconomic variables. This suggests that forecasters do not behave predominately strategically, but rather share no common belief on the adequate model of the economy.
Keywords: E37; E32; C53; C52; 330; Forecast error evaluation; consensus forecast; disagreement; uncertainty; Germany; Konjunkturprognose; Inflation; Prognoseverfahren; Bias; Risiko; Deutschland